A Geotechnical Engineering Study for the Safeguard, Restoration and Strengthening of Historical Heritage. (2016) - Cavallaro, Antonio; Grasso, Salvatore; Ferraro, Antonio
Abstract: Eastern Sicily is very rich of monuments and historical buildings, but at the same time is one of the most seismically active areas of Italy. In particular the city of Noto, which is now considered the capital of Baroque in Sicily, was destroyed by the 1693 Val di Noto Earthquake and rebuilt in another site, as in the case of some others cities. In order to study the geotechnical dynamic characteristics of the foundation soil of monuments, in situ investigations and laboratory tests have been carried out. Among in situ investigations, Borings, SPT, CPT, D-H, C-H and DMT have been carried out. Among laboratory tests, special attention has been devoted to the variation of the Young modulus non linearity, shear modulus G and damping ratio D by Cyclic Loading Triaxial tests and Resonant Column tests. This paper tries to summarize this information in a comprehensive way in order to provide a representative geotechnical model of the sites where important monuments are located.